Self-sensing cement composite for traffic monitoring in intelligent transport system - Bashir Muhmmad Tariq (Peter the Great St. Petersburg Polytechnic University, 2021)
Self-sensing cement-based composite was used to monitor the flow of traffic volume. Composite material was prepared with numerous percentages of carbon black (CB) and activated granulated ground blast furnace slag (GGBFS). This economical and concrete friendly material having piezo resistive properties helped to detect the wheel pressure induced by the vehicles passing over it. Initially, the pressure sensitivity of different mix designs was investigated in the laboratory and the samples having more sensitivity to applied load were used on the real road test for vehicle detection. Mechanical and microstructural properties of hydrated cement composite filled with CB and GGBFS as an active filler were also explored. Scanning electron microscopy/Electron dispersive spectroscopy (SEM/EDS) and X-ray diffraction (XRD) analysis were carried out to characterize the microstructure and hydration product development of different specimens at different curing ages. The tested cement composite gives a remarkable response to both compressive and vehicular loading with excellent mechanical and microstructural properties. The results also showed that the self-sensitive cement composite has a great potential to use as a device for traffic monitoring.